Advertisement Remove all ads

If (Am)N = Am .An, Find the Value Of: M(N - 1) - (N - 1) - Mathematics

Sum

If (am)n = am .an, find the value of : m(n - 1) - (n - 1)

Advertisement Remove all ads

Solution

(am)n = am .an
⇒ amn = am + n
⇒ mn = m + n               ....(1)
Now,
m( n - 1 ) - ( n - 1 )
= mn - m - n + 1
= m + n - m - n + 1      ....[ From (1) ]
= 1

Concept: Simplification of Expressions
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (C) | Q 11 | Page 101
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×